KOLABORASI ANTARA DAERAH DAN DESA DALAM PROGRAM PAK KADES MANTAB (Studi Penelitian pada Pelayanan Akta Kelahiran Online di Desa Meteseh, Kecamatan Boja, Kabupaten Kendal) - Muhammad Ilham Febriyan; Nunik Retno Herawati (Journal of Politic and Government Studies, 2026)
This study examines the collaboration between local government and village government in providing online birth certificate services through the PAK KADES MANTAB Program in Meteseh Village, Kendal Regency. The objective of this research is to analyze how the collaboration is implemented, the division of roles, and the challenges encountered in the program. This study is important as there are still many citizens who do not possess birth certificates, indicating the need for more accessible and equitable public services. This research employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation, and analyzed using collaboration theory, which includes initial conditions, processes, structure, challenges, and outcomes. The results show that the collaboration between local and village governments has improved service accessibility by bringing services closer to the community at the village level. The division of roles is relatively clear, with the local government responsible for system management and verification, while the village government directly serves the community. However, several challenges remain, including limited human resources at the village level, dependence on the local government, and technical issues such as internet connectivity. This study contributes to a better understanding that intergovernmental collaboration is crucial in improving public service delivery. The implications suggest the need to strengthen village officials’ capacity, improve infrastructure, and enhance coordination to ensure more effective and equitable services.